Price elasticities in the German Statutory Health Insurance market before and after the health care reform of 2009. Issue 5 (May 2015) - Pendzialek, Jonas B.; Danner, Marion; Simic, Dusan; Stock, Stephanie
Highlights: Price elasticities for health insurance before and after a reform were examined. Calculations are based on membership data of all sickness funds (2004–2013). Price elasticity was found to have increased more than 4-fold. The new price elasticity seems more adequate, though with unintended consequences. Abstract: This paper investigates the change in price elasticity of health insurance choice in Germany after a reform of health insurance contributions. Using a comprehensive data set of all sickness funds between 2004 and 2013, price elasticities are calculated both before and after the reform for the entire market. The general price elasticity is found to be increased more than 4-fold from −0.81 prior to the reform to −3.53 after the reform. By introducing a new kind of health insurance contribution the reform seemingly increased the price elasticity of insured individuals to a more appropriate level under the given market parameters. However, further unintended consequences of the new contribution scheme were massive losses of market share for the more expensive sickness funds and therefore an undivided focus on pricing as the primary competitive element to the detriment of quality.